KAJIAN SEMIOTIKA LIVE STREAM SAIN MANDRA: SEMIOTIC STUDY OF SAIN MANDRA'S LIVE STREAM - Dave Johsua M. Rumengan; Elda Franzia Jasjfi; Acep Iwan Saidi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2026)
Semiotic Design Study Of Sain Mandra's Live Stream. Since the end of the COVID-19 pandemic, the phenomenon of Mobile Legends game live streaming has become a captivating topic of discussion. However, many streamers still neglect the visual aspects that their audience will view during live streams. This research highlights the importance of attention to visual structure from the beginning to the end of a live stream. The primary goal of this study is to explain the levels of denotative and connotative signs in the visual structure of Sain Mandra's live stream design, which influence the visual form of a live stream, and to identify the interrelated visual signs that build the message and meaning of a live stream. By utilizing Roland Barthes' semiotic theory, this research aims to uncover the meanings and signs present in the context of live streaming. The implications of the live stream design discussed in this study reveal the emergence of a myth that portrays the ideology that live streaming can contribute to education. The results of this research present the signs and meanings of Sain Mandra's visual live stream, which play a role in shaping an ideology that can benefit both streamers and their audience.